Etika Aparatur Pemerintah Daerah dalam Pelayanan Adminsitrasi Kependudukan Masa Pandemi Covid-19 Di Kantor Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Mempawah - Bima Sujendra; Nahot Tua Parlindungan Sihaloho (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2021)
Abstract: This study conducted a study of the Ethics of Local Government Apparatuses in Population Administration Services at the Mempawah Regency Population and Civil Registration Office during the Covid 19 Period. The formulation of the problem in this study is how the ethics of local government officials in the service of making Electronic ID cards at the Population and Registration Office Civil Society of Mempawah Regency during the Covid 19 period. The research method used by researchers is a qualitative approach, with data collection techniques through observation, interview documentation. The theory used to analyze in this research is the Indicators of State Administration Ethics according to Surjadi, which consists of Honesty, Fairness, Obedience to Rules, Responsibility, and Fairness. The results showed that the Honesty aspect was good; this was seen from the absence of illegal levies and did not cover up the complaints obtained from the community related to being unsatisfactory in providing services. The justice aspect is not good because there is still discrimination in providing services to the community. Aspects of Obeying the Rules are still not good; this can be seen from the apparatus that does not obey the regulations, namely the discipline of working hours. Aspects of Fairness and Property are still not good, and this can be seen from the lack of friendliness of the apparatus in serving the public who ask questions related to information on making and taking Electronic ID cards. The advice given by the researcher is that the Disdukcapil of Mempawah Regency is expected to increase awareness to be ethical in providing services by making SOPs related to being ethical in providing services during the covid 19 periods.